2017
DOI: 10.1007/s00520-017-3854-x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic literature review of the efficacy, effectiveness, and safety of filgrastim

Abstract: Purpose Filgrastim (NEUPOGEN ® ) is the originator recombinant human granulocyte colony-stimulating factor widely used for preventing neutropenia-related infections and mobilizing hematopoietic stem cells. This report presents findings of a systematic literature review and meta-analysis of efficacy and safety of originator filgrastim to update previous reports. Methods A literature search of electronic databases, congress abstracts, and bibliographies of recent reviews was conducted to identify English-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 52 publications
2
44
0
4
Order By: Relevance
“…Availability of the first recombinant human granulocyte-colony stimulating factor (rhG-CSF) in the 1990s (filgrastim) provided a safe and effective means to reduce the considerable burden of infection-related morbidity and mortality associated with chemotherapy-induced neutropenia (CIN). 1 The advent of pegfilgrastim, the first long-acting rhG-CSF, a decade later simplified supportive care for CIN with a once-per-chemotherapy-cycle option. 2 Since then, supportive care options for CIN have not changed other than through the introduction of biosimilar alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…Availability of the first recombinant human granulocyte-colony stimulating factor (rhG-CSF) in the 1990s (filgrastim) provided a safe and effective means to reduce the considerable burden of infection-related morbidity and mortality associated with chemotherapy-induced neutropenia (CIN). 1 The advent of pegfilgrastim, the first long-acting rhG-CSF, a decade later simplified supportive care for CIN with a once-per-chemotherapy-cycle option. 2 Since then, supportive care options for CIN have not changed other than through the introduction of biosimilar alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta‐analysis of nine randomised clinical trials including 2197 patients (filgrastim, n= 1130; placebo or no treatment, n = 1067) showed that the use of filgrastim led to a decrease in FN incidence (relative risk [RR] 0.63, 95% CI 0.53‐0.75), a result further confirmed in two observational studies . A meta‐analysis of five randomised clinical trials and one non‐randomised clinical trial with a total of 1409 patients (filgrastim, n = 714; placebo or no treatment, n = 695) reported a decreased incidence in grade 3/4 neutropenia with filgrastim (RR 0.50, 95% CI 0.37‐0.68) …”
Section: Discussionmentioning
confidence: 93%
“…The authors reported a reduction in the incidence of FN and in the number of G3‐4 neutropenia events, with a decreased duration of neutropenia in favour of patients treated with filgrastim. The use of G‐CSFs led to a decrease, albeit not significant, in the incidence of infections, use of antibiotic therapy and hospitalisation . In all of the above studies, patients receiving filgrastim showed better maintenance of the planned dose and better compliance with administration timing.…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…El r-met-hu G-CSF no glicosilado, conocido comercialmente como Filgrastim, ha sido utilizado con éxito para estimular la proliferación y la maduración de células hematopoyéticas (Dale et al, 2017). Sin embargo, el papel fisiológico del r-met-hu G-CSF en otros tejidos no hematopoyéticos, tales como el tejido testicular, así como su efecto en la proliferación y diferenciación de las células que lo componen es una incógnita.…”
Section: Introductcionunclassified